Paddy residue based power generation in Malaysia: Environmental assessment using LCA approach - Mohd Shafie, Shafini (Asian Research Publishing Network (ARPN), 2015)
Malaysia is pleasant by plenty of biomass resources that can possibly be consumed as a supply of electricity production.One of them is paddy residues. Annually about 3.66 million tonne of paddy residue is left in the fields.Towards year 2020 this value is forecasted to increase to 7 million tonne per year due to emerging technology development in agriculture industries. Paddy residue can potentially be used as feedstock fuel for electricity generation in Malaysia. Paddy residue based power generation not simply might resolve the difficult of eliminating rice straw from paddy fields without open burning, but furthermore might decrease GHG emission that donate to climate change, acidification, and eutrophication, and amongst another ecological harms.Rice husk power generation would emit a total of 0.217 kg CO2/kWh, whereas rice straw results in some 0.43 kg CO2/kWh.These emission is smaller than conventional power generation in Malaysia.